Evaluation of Antibacterial Properties of Dental Adhesives Containing Metal Nanoparticles - Shafiei F; Ashnagar A; Ghavami-Lahiji M; Najafi F; Amin Marashi SM (Shiraz University of Medical Sciences, 2018)
Statement of problem: Secondary dental caries is a common clinical finding in composite restoration. The development of a bactericidal dental adhesive provides a promising method to reduce the risk of secondary caries. Objectives: This study aimed to assess the antibacterial activity of silver (Ag) and titanium dioxide (TiO2) nanoparticles incorporated into an experimental dentin bonding agent formulation. Materials and Methods: Ag and TiO2 nanoparticles at 0.05, 0.1, 0.2, 0.5, and 1 wt% concentrations were incorporated into the adhesives. The suspensions were sonicated to ensure homogenous dispersion of nanoparticles in the adhesive system. Formulation was composed of acetone, 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenyl]propane (Bis-GMA), 1,6-bis-[2-methacryloyloxyethyl carbonyl amino]-2,4,4-trimethylhexane (UDMA), trimethylolpropane trimethacrylate (TMPTMA), 2-hydroxyethyl methacrylate (HEMA), and photoinitiator, with polyvinylpyrrolidone (PVP) as the stabilizer. We counted the colony-forming units (CFU%) of two cariogenic bacteria, Streptococcus mutans (S. mutans) and Lactobacillus acidophilus (L. acidophilus), that were exposed to the powdered light cured adhesive specimens. The effects of various concentrations of each nanoparticle were compared by one-way ANOVA, followed by the post hoc Bonferroni test. Results: All samples exhibited definite antibacterial activity (P<0.05) compared to the control specimens. The Ag nanoparticle samples showed higher antibacterial properties compared to the TiO2 nanoparticle samples. Increasing the concentration of nanoparticles resulted in significant differences in bactericidal properties, with the exception of 0.2 to 0.5 wt% Ag nanoparticle specimens exposed to S. mutans and the 0.2 to 0.5 wt% TiO2 nanoparticle specimens exposed to L. acidophilus. Conclusions: These metal-based nanoparticles exhibited dose-dependent bactericidal activities. The Ag nanoparticles had higher antibacterial activity compared to the TiO2 nanoparticles. Incorporation of these nanoparticles into dental adhesives is a promising way to reduce the risk of secondary caries. However, further clinical evaluations should be performed.